TIME ORIENTATION OF PERSONALITY PROVIDED UNDER THE CONDITIONS OF ATO - Павленко, Оксана Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
The article analyzes the notion of a balanced perspective of the individual. Its value is defied for a person who is in diffiult life circumstances. The attitude of the person in the ATO to the time space of his own life is analyzed. There are three main groups of respondents in the ATO zone, in particular military ATOs, settlers and residents of the «gray zones». The preferred orientation of respondents for a certain time of their own life was revealed. Comparison of time orientation with respondents living in stable territories is made. It is determined that the focus on the future is typical only for representatives of the control group, all respondents related to the ATO are oriented predominantly at the present time, that is, they live «here and now». The associative number of respondents related to a certain time has been analyzed. It has been determined that the past is often associated with emotions by the respondents, the present is related to actions, and the future is with meanings. For settlers there is mostly a positive associative connection to the past, and for the military ATOs and residents of the border areas - with the future. The degree of satisfaction with the past, present and future time is determined. It was diagnosed that the smallest satisfid with their own lives are settlers and residents of the border with the zone of ATO territories. Most respondents of these groups are not satisfid with the present moment of life. However, the attitude towards the future for these categories is more optimistic than for the representatives of the control group, which may be due to the non-realism of the prospect of the future. For military ATOs characterized by high satisfaction with all the time space of their own lives, which may be due to the situation of direct involvement in hostilities, which may endanger the lives of respondents. The prospect of our study is to develop programs for facilitating the acceptance and transformation of our own temporal continuum for each of the presented categories of respondents located in the ATO zone.